Hubungan antara Kecerdasan Emosi dengan Gaya Pengurusan Konflik di Kalangan Kakitangan di JKR Malaysia - Su Faizah, Sukor (2009)
The purpose of this study is to investigate the correlation between emotional intelligence and conflict management style among the JKR’s staff. This study also aimed at determining whether emotional intelligence dimensions which are intrapersonal skills, interpersonal skills, stress management, adaptability and general mood predict the variance in conflict management style among the Professional and Management staffs in JKR. Out of 534 questionnaires distributed,only 203 respondents returned the questionnaires. The data was analyzed using ”Statistical Package for Social Science” (SPSS)version 15. The result shows that the level of interpersonal skills and adaptability are high. Analysis using Pearson correlation indicates from all the five dimensions, only three factors in emotional intelligence which are interpersonal skills, adaptability and general mood have a significant correlation with conflict management style. In addition, multiple regression analysis shows that only adaptability and stress management significantly can influence conflict management style with the value of adjusted R2 is 0.221. Therefore, JKR should stress on adaptability and stress management in order to enhance conflict management style among the staff.